Judicialização da educação no Brasil: tendências da produção do conhecimento e perspectivas para a exequibilidade do direito (2000-2010) - Pires, Diego Bruno de Souza (2017)
This research deals with judicialization of education, highlighting the characteristics of academic productions produced by postgraduate programs in Brazil from 2000 to 2010, and the perspectives to understand this phenomenon, especially for the feasibility of the right to education. Thus, we aim to analyze - in a systematic way - the academic productions about the judicialization of education produced by the postgraduate programs in education in Brazil and to qualify the possible changes in the focuses and dimensions of these productions in the period from 2000 to 2010, as well as mapping these productions to characterize their directions and understanding to the possible contributions to the constitution of educational policies. This is a qualitative study of the state of knowledge and, therefore, seeks to apprehend the tendencies in academic production based on thematic categories, exploring the repertoire of the selected texts, their argumentative characteristics, theoretical and methodological options and context. It has as a north a historical understanding of the right to education, from the understanding brought by Norberto Bobbio. In this approach, the right to education, the Judicialization and the Reservation of the possible were chosen as categories of analysis. In the analyzed productions the diversity of dimensions and terminologies are perceived, defending the judicialization as an instrument that imposed access to school, but, at the same time, it has become a phenomenon that for some time has extrapolated this limit, to cover thematic and diverse approaches such as the quality of education and education, and also to stimulate fronts of interventions such as supervising, interfering and formulating public policies and, in some cases, controlling didactics and school pedagogy, mitigating executive skills.